Factors Affecting the Implementation of Green Procurement in Indonesia Construction Industry - Novilia Hardiani; Tri Joko Wahyu Adi (Institut Teknologi Sepuluh Nopember, 2017)
A construction industry is often described as inefficient, irresponsible towards environment and society. This research aimed to analyze the factors affecting the implementation of green procurement in Indonesia construction industry. The research project specifically focuses on a construction material procurement. For this purpose, 26 factors were identified and project managers who worked on construction companies with large grade of national / international scales belonging to the association of construction in Surabaya were interviewed. The relative importance on these factors were quantified by Relative Importance Index and Confidence Interval. The result showed that the factors affecting implementation of green procurement in Indonesia construction industry were requirement document (contract) and cost efficient from energy and waste saving.